Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3844/jssp.2011.529.537
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of High School Students toward Physical Education and Their Sport Activity Preferences

Abstract: Problem statement: Identifying and understanding correlates of school children's physical education activity participation are critical to promoting current and lifelong physical activity participation of children. Among other factors, children's attitudes are considered to be a key element influencing physical activity participation. Children who have more positive attitudes toward physical activity are reported to be more likely to participate in physical activity outside of school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 25 publications
(27 reference statements)
3
31
2
4
Order By: Relevance
“…Estas respuestas llevan hacia dos vertientes, por un lado, el gusto por una asignatura práctica y que resulta similar a lo expresado por Hernández et al (2007) y también por Piéron et al (2008); por otro lado, a cómo se negocia un currículum y cómo se acepta seguir una línea de actuación por preferencias del alumnado que supone una mejora en la participación, tal y como se ha aportado en otros estudios (Dyson, 2006;Fisette, 2013;Zeng et al, 2011). Una de las preguntas abiertas en el cuestionario fue ¿qué es lo que más le gusta de la clase de EF?…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…Estas respuestas llevan hacia dos vertientes, por un lado, el gusto por una asignatura práctica y que resulta similar a lo expresado por Hernández et al (2007) y también por Piéron et al (2008); por otro lado, a cómo se negocia un currículum y cómo se acepta seguir una línea de actuación por preferencias del alumnado que supone una mejora en la participación, tal y como se ha aportado en otros estudios (Dyson, 2006;Fisette, 2013;Zeng et al, 2011). Una de las preguntas abiertas en el cuestionario fue ¿qué es lo que más le gusta de la clase de EF?…”
Section: Resultados Y Discusiónunclassified
“…(Carlson, 1995;Cuevas, Contreras, & García-Calvo, 2012;Moreno & Cervelló, 2003;Zeng, Hipscher, & Leung, 2011). Todo ello hace que las creencias y actitudes positivas y negativas sean variadas y diferentes entre el alumnado.…”
Section: Introductionunclassified
“…According to the TPB, attitudes, along with subjective norms and perceived behavioral control, are significant predictors of future behaviors. It is important to further our understanding of attitudes and how they relate to the TPB as research in physical education has indicated that students' attitudes could influence future participation in physical activity (Carlson, 1995;Ennis, 1996;Silverman & Subramaniam, 1999;Subramaniam & Silverman, 2000;Zeng, Hipscher, & Leung, 2011). Students with positive attitudes toward physical education also are more likely to participate in physical activity outside of school (McKenzie, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Physical education (PE) in school directly affects physical activity (PA) of a child in general, as well as the adoption of healthy lifestyle in general (Jusisin, Malcic & Kostovic, 2017). The primary objective of physical education is developing positive attitudes in children to promote lifelong physical activity (Chatterjee, 2013;Sollerhed, Ejlertsson & Apitzsch, 2005;Zeng, Hipscher & Leung, 2011). Regular PA has enormously positive effects on well-being, and different health dimensions: biological as well as mental, emotional and social (Strong et al 2005).…”
Section: Introductionmentioning
confidence: 99%